Think locally, act locally: spillovers, spillbacks, and efficient decentralized policymaking - Hikaru Ogawa; David E. Wildasin (Center for Economic Studies and ifo Institute (CESifo), 2007)
In this paper, we analyze a class of models in which there are interjurisdictional spillovers among heterogeneous jurisdictions, as illustrated for instance by CO2 emissions that affect the global environment. Each jurisdiction's emissions depend upon the local stock of private capital. Capital is interjurisdictionally-mobile and may be taxed to help finance local public expenditures. We show that decentralized policymaking leads to efficient resource allocations in important cases, even in the complete absence of corrective interventions by higher-level governments or coordination of policy through Coasian bargaining. In particular, even when the preferences and production technologies differ among the agents, the decentralized system can still result in globally efficient allocation.
Keywords: H23; H77; Q58; 330; Grenzüberschreitende Umweltbelastung; Umweltschutz; Spillover-Effekt; Rechtsordnung; Politische Entscheidung; Allokation; Theorie